Longitudinal Analysis of Social Support and Emotional Control Among Engineering Students in Vietnam” (Indo-American Journal of Life Sciences and Biotechnology, 2025)
Within the setting of Vietnam National University Ho Chi Minh City, this research explores the complex link between students' perceptions of social support and their involvement in emotion regulation. This study uses a quantitative technique to reveal complex patterns and relationships by drawing data from 675 individuals in a thorough survey. The results show that there is a complex pattern to how students regulate their emotions; students who identify as male show more involvement and mostly use techniques that focus on self-support and emotional awareness. Importantly, individuals' reported levels of social support were moderate on the whole, with friends being the most common source. The effect of educational settings is highlighted by differences in the level of involvement in emotion regulation, especially among engineering students. Students' emotional coping mechanisms are shaped by their families and significant others, as the research shows that there is a positive association between perceived social support and the frequency of participating in behavior control measures. In light of these findings, it is clear that educational environments need individualized treatments to help students develop stronger social support networks and better control their emotions. Finally, this study highlights the need for strategies that strengthen social support systems and emotion management skills in educational settings, and it contributes to students' holistic development by emphasizing the significance of fostering an environment that supports students' emotional well-being alongside their academic pursuits